Stock valuation training for potential millennial investors - Rafik, Abdur (Universitas Muhammadiyah Magelang, 2021)
The debate about whether investment managers have better stock-picking skills than the market has been going on for a long time. Many cross-country studies have shown that professional investment managers cannot produce better portfolio performance than randomly selected investors. This empirical fact is counterproductive considering that investment managers are managers of public funds and indicate that their skills in selecting stocks are questionable. This poor skill can be sourced from their low valuation knowledge and skills so that stock price movements cannot be projected accurately. This training was designed to educate and train the skills of prospective millennial investors in conducting stock valuations. Participants consisted of 22 people who came from millennials, ranging from students to professional workers. The training is conducted online for a full day. Training achievement was evaluated using pre-test and post-test. The evaluation showed that the knowledge and skills of participants in conducting stock valuation increased after attending the training. In order to ensure success and maintain the continuity of the skills that have been acquired, these prospective millennial investors need to be encouraged to be actively involved as professional investors in the capital market.